Aerosol optical, microphysical and radiative forcing properties during variable intensity African dust events in the Iberian Peninsula - Fern??ndez, Alfonso; Molero, Francisco; Salvador, Pedro; Revuelta, Arantxa; Becerril-Valle, Marta; Gomez-Moreno, Francisco Javier; Art????ano, Bego??a; Pujadas, Manuel (Atmospheric Research, 2017)
Aerosol measurements at two AERONET (AErosol RObotic NETwork) sites of the Iberian Peninsula: Madrid (40??.45N, 3.72W) and La Coru??a (43??.36N, 8??.42W) have been analyzed for the period 2012???2015 to assess aerosol optical properties (intensive and extensive) throughout the atmospheric column and their radiative forcing (RF) and radiative forcing efficiency (RFeff) estimates at the Bottom and Top Of Atmosphere (BOA and TOA respectively). Specific conditions as dust-free and African dust have been considered for the study. Unprecedented, this work uses the quantification of the African dust aerosol at ground level which allows us to study such AERONET products at different intensity levels of African events: Low (L), High (H) and very high (VH). The statistical difference between dust-free and African dust conditions on the aforementioned parameters, quantified by means of the non-parametric Kolmogorov-Smirnov test, is quite clear in Madrid, however it is not in La Coru??a. Scattering Angstrom Exponent (SAE) and Absorption Angstrom Exponent (AAE) were found to be 1.64 ?? 0.29 and 1.14 ?? 0.23 respectively in Madrid for dust-free conditions because typical aerosol sources are traffic emissions and residential heating, and black carbon is an important compound in this aerosol kind. On the other hand, SAE and AAE were 0.96 ?? 0.60 and 1.44 ?? 0.51 for African dust conditions in this location. RF (at shortwave radiation) seems to decrease as the African dust contribution at ground level is larger which indicates the cooling effect of African dust aerosol in Madrid. We have also proved the potential of a 2D-cluster analysis based on AAE and SAE to differentiate both situations in Madrid. Conversely, it is suggested that aerosols observed in La Coru??a under dust-free conditions might come from different sources. Then, SAE and AAE are not good enough indicators to distinguish between dust-free and African dust conditions. Besides, as La Coru??a is at a further distance than Madrid from the African dust source it is ...